Synthesis and antitumor activity of novel 2-substituted indoline imidazolium salt derivatives. Issue 5 (10th December 2014) - Xu, Xiao-Liang; Yu, Chun-Lei; Chen, Wen; Li, Ying-Chao; Yang, Li-Juan; Li, Yan; Zhang, Hong-Bin; Yang, Xiao-Dong
Abstract : A series of novel 2-substituted indoline imidazolium salt derivatives were synthesized and their antitumor structure–activity relationship studies were reported. Abstract : A series of novel 2-substituted indoline imidazolium salt derivatives has been prepared and evaluated in vitro against a panel of human tumor cell lines. The results suggest that the existence of a substituted benzimidazole ring and substitution of the imidazolyl-3-position with a naphthylacyl or 2-naphthylmethyl group were vital for modulating the cytotoxic activity. Compound25 was found to be the most potent derivative with IC50 values of 0.24–1.18 μM, and exhibited cytotoxic activity selectively against MCF-7, SW480, SMMC-7721 and HL-60 cell lines, while compound26 showed powerful inhibitory activities selectively against SMMC-7721 and A549 cell lines. Compound25 can induce G2/M phase cell cycle arrest and apoptosis in SMMC-7721 cells.